1999
DOI: 10.1017/s030500419800334x
|View full text |Cite
|
Sign up to set email alerts
|

Fractional integration, differentiation, and weighted Bergman spaces

Abstract: We study the action of fractional differentiation and integration on weighted Bergman spaces and also the Taylor coefficients of functions in certain subclasses of these spaces. We then derive several criteria for the multipliers between such spaces, complementing and extending various recent results. Univalent Bergman functions are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Recall that a sequence {λ k } is of bounded variation if . But this contradicts Theorem 1.3 of [3]. This contradiction proves the Claim above.…”
Section: Remarkmentioning
confidence: 68%
See 2 more Smart Citations
“…Recall that a sequence {λ k } is of bounded variation if . But this contradicts Theorem 1.3 of [3]. This contradiction proves the Claim above.…”
Section: Remarkmentioning
confidence: 68%
“…We also mention the paper [19] which contains related, precursor results to those in [3]. In Theorem 1.3, part (a), of [3], it is shown that the sequence {k …”
Section: Remarkmentioning
confidence: 95%
See 1 more Smart Citation
“…This is a particular case of Theorem 2.1 of [6] and follows from the work of Flett [12,13]. In view of this result and (1.2), it is natural to ask whether the inclusion B(p, 2) ⊂ A 2p (0 < p < ∞) holds.…”
Section: Letmentioning
confidence: 88%
“…Let p and α be as in the statement and f (z) = ∞ n=0 a n z n ∈ Ᏸ So using [6, Lemma 1.1] (see also [12, part (iii) of Theorem 5]) and [6,Corollary 3.5], we deduce that the fractional integral…”
mentioning
confidence: 99%